Cerebral abscess complicating embolization of an arteriovenous malformation: Case report and review of litera - Khoshnevisan, Alireza (Iran J Neurol, 2014)
Central nervous system infection is a rare complication of endovascular procedures. We report a 21-year-old woman presented with headache, nausea, vomiting, and right-sided hemiparesis 4 months after endovascular embolization of cerebral arteriovenous malformation. Investigations led to the diagnosis of multiple brain abscesses. This is the sixth case report of brain abscess following endovascular interventions.